On Generalized Fibonacci Hybrinomials - Taşyurdu, Yasemin; Şahin, Ayşe (Communications in Mathematics and Applications, 2022)
In this paper, we define generalized Fibonacci hybrinomials, which are generalization of both Fibonacci type hybrinomials and Lucas type hybrinomials. We introduce these hybrinomials in two types as generalized Fibonacci type hybrinomials and generalized Lucas type hybrinomials. We obtain matrix representations, Binet formulas, generating functions and some properties of the generalized Fibonacci hybrinomials. Moreover, we give relationship between the generalized Fibonacci type hybrinomials and generalized Lucas type hybrinomials.
Keywords: Fibonacci polynomial; Lucas polynomial; Fibonacci hybrinomial; Lucas hybrinomial